New strategies for synthesis and immobilization of methalophtalocyanines onto kaolinite: Preparation, characterization and chemical stability evaluation. (November 2016) - da Silva, Tiago Honorato; de Souza, Thalita F.M.; Ribeiro, Anderson Orzari; Calefi, Paulo Sergio; Ciuffi, Katia Jorge; Nassar, Eduardo José; Molina, Eduardo Ferreira; Hamer, Peter; de Faria, Emerson Henrique
Abstract: This study presents results concerning the one-step synthesis and immobilization of a metallophthalocyanine on kaolinite as support/catalyst. X-ray diffractometry (XRD), nuclear magnetic resonance (NMR) and infrared (FTIR), UV/Visible (UV/Vis) and X-ray photoelectron (XPS) spectroscopies, thermal analyses, textural analyses (BET) and scanning electron microscopy (SEM) aided for the characterization of the materials. The FTIR, XPS and UV/Vis absorption spectra confirmed metallophthalocyanine formation. XRD analysis provided data on the structural disorganization of kaolinite during the synthesis of metallophthalocyanine, corroborated by SEM. NMR revealed that partial dissolution of aluminum from the octahedral kaolinite sheets was possible, which should release Al into the medium and, together with phthalonitrile, promote cyclomerization of the phthalocyanine macrocycle. Graphical abstract: Highlights: Cyclomerization reaction was successfully employed using kaolinite as metal source. All the characterization techniques confirm the synthesis of phthalocyanine. The chemical stability of the materials obtained were investigated. The synthesis presented herin reduces the agglomeration of complexes.